Construction of new alternative transmission sites by incorporating structure-defect metal-organic framework into sulfonated poly(arylene ether ketone sulfone)s. (3rd August 2021) - Zhang, Zhenguo; Ren, Jiahui; Ju, Mengchi; Chen, Xuan; Xu, Jingmei; Wang, Zhe; Meng, Lingxin; Zhao, Pengyun; Wang, Hao
Abstract: Metal-organic frameworks are new kinds of porous crystalline materials. The Zr-based metal-organic framework (MOF-801) is consists of [Zr6 (u3 -O)4 (u3 -OH)4 ] 12+ clusters and fumaric acid connectors. MOF-801 has excellent mechanical properties, high chemical stability and high water absorption capacity. There are a large number of hydrophilic functional groups inside MOF-801, which is effective to promote interfacial compatibility between MOF-801 and polymer matrixes. In this work, the MOF-801 with structural defects was synthesized through the solvothermal method by adding excess formic acids as the regulator. These structural defects could confer MOF-801 high surface area (2476.34 m 2  g −1 ) and promote the water absorption capacity. Moreover, structural defects could also expose more open metal sites of MOF-801, thereby increasing the Lewis acidity of MOF-801. Then, the hybrid membranes were synthesized by combining the MOF-801 with structural defects and C-SPAEKS. Dense hydrogen-bond networks formed between the MOF-801 and C-SPAEKS further promote enhance proton conductivity. At the condition of 90 °C and 100% relative humidity, the highest proton conductivity of hybrid membranes reached 0.100 S cm −1, which is similar to that of Nafion 117. Meanwhile, these hybrid membranes showed outstanding chemical and thermal stabilities. These results indicate that these hybrid membranes have potential as proton exchange membranes. Graphical abstract: The synthesized structure-defect MOF-801 has uniform crystal size, and hybrid membranes show good proton conductivities because of hydrogen-bond networks between C-SPAEKS and MOF-801 can provide hopping sites for protons. Image 1 Highlights: MOF-801 with good water absorption and chemical stability was synthesized. Hybrid PEMs with enhanced proton-conducting performance were prepared. Hydrogen-bonds between MOF-801 and C-SPAEKS construct new proton transport channels. Open metal sites (Zr 4+ ) promote protonation of H2 O and then enhance proton transfer.